Reconstruction of infrarenal abdominal aortic occlusion using the Culotte stenting technique: a case report - D. A. Feshchenko; G. S. Zasypkin; B. A. Rudenko; D. K. Vasiliev; F. B. Shukurov; А. S. Shanoyan; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2022)
Patients with clinically significant infrarenal abdominal aortic atherosclerosis are often encountered in the clinical practice of vascular and endovascular surgeons. In the absence of timely treatment, the ability to work and life quality of patients are sharply reduced, and in some cases, patients require limb amputation. Until recently, the only treatment option for such a lesion was an open surgery. However, a good skill level of endovascular surgeons and the device availability allow today to perform minimally invasive operations with comparable effectiveness and greater safety in comparison with open surgery. We present a case report of successful endovascular treatment of aortic occlusion involving the right and left common and external iliac arteries using Culotte stenting technique with further 12-month follow-up.